Liver ultrasound elastography: More than staging the disease - Gherlan, George S (World J Hepatol, 2015)
Ultrasound elastography is perhaps the most important breakthrough in the evolution of ultrasonography in the last 15 years. Since transient elastography was introduced, many other methods have been developed and became more and more widely available. The value of ultrasound elastography in staging a chronic liver disease has been established by numerous studies. There have been many studies that have shown that using liver elastography it is possible to predict the presence of the complications of cirrhosis: portal hypertension, presence of esophageal varices (and even their risk of bleeding) and hepatocellular carcinoma. It has been shown that liver elastography can predict the progression of liver fibrosis and also the survival (hepatic events - free) of the patients with chronic liver diseases. These are the real quests of the clinicians, this is the ultimate scope of any medical investigation - to predict the outcome of a patient and to help making therapeutic decisions. I brought together only a small amount of the data that has already been written on this subject to support my affirmation that liver ultrasound elastography is more than a tool for staging the liver disease, but it is also comparable to a crystal ball which in the hands of a skilled clinician can reveal the future of the patient and can help to improve this future.